The Bilingual Muse Self-Translation among Russian Poets - Wanner, Adrian (Northwestern University Press, 2020)
The Bilingual Muse analyzes the work of seven Russian poets who translated their own poems into English, French, German, or Italian. Investigating the parallel versions of self-translated poetic texts by Vladimir Nabokov, Joseph Brodsky, Andrey Gritsman, Katia Kapovich, Marina Tsvetaeva, Wassily Kandinsky, and Elizaveta Kul'man, Adrian Wanner considers how verbal creativity functions in different languages, the conundrum of translation, and the vagaries of bilingual identities. Wanner argues that the perceived marginality of self-translation stems from a romantic privileging of the mother tongue and the original text. The unprecedented recent dispersion of Russian speakers over three continents has led to the emergence of a new generation of diasporic Russians who provide a more receptive milieu for multilingual creativity.